Antecedents and outcomes of effectuation among the workforce of small and medium-sized enterprises - Rathakrishnan, Thanuja (2018)
For many years, innovation is known as an ‘antidote’ towards organizations sustainability and survival. Nonetheless, the small and medium sized enterprises (SMEs) in Malaysia is suffering from low innovation, which stems from the lack of innovative behavior. In an environment where change is pervasive and unpredictable, innovation serves as a necessity for firms to compete in. Little attention, however, has been given to the employees’ decision making and its impact on innovative behavior. The main objective of this research is to identify antecedents and outcomes of effectuation decision making logic to enhance the innovative behavior in SMEs. In order to answer the research question, this study looks into the underpinning theories of Person – Organization Fit and Effectuation. These theories suggest that the congruence of employees’ values (i.e openness to change or self-transcendence) and the SMEs’ organization culture (i.e. adhocracy or clan) would enable the workforce to use effectuation decision making effectively, which has been shown to work better under the uncertain conditions that surrounds SMEs. This would then lead to enhanced innovative behavior among the workforce that may translate to firm performance, with the intervention of Knowledge Management Orientation (KMO). Survey questionnaires were distributed to the SME workforce in Selangor whose nature of their work involves decision making and the process of innovation. The study found that adhocracy mediates between openness to change and effectuation; effectuation mediates between individual values and innovative behavior and KMO mediates between innovative behavior and firm performance. Clan, however, shows no mediation between self-transcendence and effectuation. Overall, this study achieved the main research objective which is on the antecedents and outcomes of effectuation. The antecedents are openness to change, self-transcendence, and adhocracy whereas the outcomes are innovative behaviour and firm performance. Also, the mechanism from how the antecedents (openness to change and self-transcendence individual values) lead to outcomes (firm performance) was uncovered. This study implies that effectuation indeed enhance the innovative behavior of the SME workforce. For that to happen, the SMEs must ensure that the information and ideas are managed carefully in a system to improve the firm performance. To encourage more effectuation use, individual value of openness to change and selftranscendence and organization culture of adhocracy should be cultivated. This study adds nuance to our understanding that effectuation theory works well in a dynamic environment such as the SMEs. This is due to the flexibility in the logic itself that is less rigid and structured in the face of high uncertain environment. Knowing effectuation leads to positive outcomes, this study looks at the compatibility of the workforce and the organizational culture based on the P-O fit theory. Since this study found effectuation would achieve high innovation, this logic can be introduced in selection and hiring candidates, trainings, and business education, which is in line with the Industrial Revolution 4.0 (IR 4.0).